The first Asian species of Polycaon Castelnau, and a new montane species of Melalgus Dejean from China (Coleoptera: Bostrichidae: Polycaoninae) - Liu, Lan-Yu; Beaver, Roger A. (Zootaxa, 2023)
We describe Polycaon sinensis sp. n., the first Asian species of this otherwise American genus, and Melalgus plesiobatillus sp. n., from the same montane locality in China (Zhejiang). The following new synonym is proposed: Melalgus batillus (Lesne) (=Melalgus japonicum Chûjô syn. n.). We comment on the species, Melalgus borneensis (Lesne) sensu Borowski & Węgrzynowicz (2012), and provide a key to the Chinese species of Polycaoninae.